European Journal of Scandinavian Studies (De Gruyter, 2010)
The journal's content reflects the international spectrum of Scandinavian studies with the subareas of modern literature and cultural studies (including media studies), medieval studies and linguistics. The journal adresses scholars of literature and linguistics as well as scholars of comparative literature interested in this field.